Quantification of the Central Cardiovascular Network Applying the Normalized Short-time Partial Directed Coherence Approach in Healthy Subjects - Schulz, Steffen; Bolz, Mathias; Bär, Karl-Jürgen; Voss, Andreas (Methods of Information in Medicine, 2018)
Background: The central control of the autonomic nervous system (ANS) and the complex interplay of its components can be described by a functional integrated mode – the central autonomic network (CAN). CAN represents the integrated functioning and interaction between the central nervous system (CNS) and ANS (parasympathetic and sympathetic activity).Objective: This study investigates the central cardiovascular network (CCVN) as a part of the CAN, during which heart rate (HR), systolic blood pressure (SYS) and frontal EEG activity in 21 healthy subjects (CON) will be analysed. The objective of this study is to determine how these couplings (central-cardiovascular) are composed by the different regulatory aspects of the CNS-ANS interaction.Methods: To quantify the short-term instantaneous causal couplings within the CCVN, the normalized short time partial directed coherence (NSTPDC) approach was applied. It is based on an m-dimensional MAR process to determine Granger causality in the frequency domain.Results: We found that CCVN were of bidirectional character, and that the causal influences of central activity towards HR were stronger than those towards systolic blood pressure. This suggests that the central-cardiac closed-loop regulation process in CON focuses mainly on adapting the heart rate via the sinoatrial node rather than focusing on SYS. The CNS-ANS coupling directions with respect to central spectral power bands were characterized as mostly bidirectional, where HR and SYS acted as drivers in nearly every frequency band (unidirectional for α, α1 and α2).Conclusion: This study provides a more indepth understanding of the interplay of neuronal and autonomic cardiovascular regulatory processes in healthy subjects, as well as a greater insight into the complex CAN.
Keywords: Autonomous nervous system; causal coupling analysis; central cardiovascular network; central autonomic network; partial directed coherence